Impact of Chemically Treated Waste Rubber Tire Aggregates on Mechanical, Durability and Thermal Properties of Concrete - Khern, Yih Chen; Paul, Suvash Chandra; Kong, Sih Ying; Babafemi, Adewumi John; Anggraini, Vivi; Miah, Md Jihad; Šavija, Branko (Frontiers in Materials, 2020)
Abstract Studies have shown that the incorporation of waste tyre rubber aggregates reduces the strength, increases permeability and decrease thermal conductivity of concrete. However, only a few studies have investigated the effect of surface-modified rubber aggregates on the properties of concrete. This study investigates the effect of the surface treatment of waste tyre rubber as coarse aggregates with different oxidizing solutions and different treatment durations on the mechanical, durability and thermal properties of concrete. The properties of concrete incorporated with 8% rubber coarse aggregates (by volume of natural aggregates) which were treated with three different solutions: water (H2O), 20% sodium hydroxide (NaOH) and 5% calcium hypochlorite [Ca(ClO)2] (both as % weight of water) for durations of 2, 24 and 72 hrs, respectively. The effect of these treatments on the compressive strength, splitting tensile strength, water permeability, thermal conductivity and diffusivity of concrete was investigated. Results show that Ca(ClO)2 has a more positive effect on the strength and permeability compared to NaOH solution and water. Experimental results were statistically analyzed using ANOVA and Post-Hoc tests. The analyses showed that the improvement of concrete strength is only significant when the treatment with NaOH and Ca(ClO)2 is prolonged to 72 hrs. Furthermore, the microstructural analysis of concrete showed that the improvement in the strength is due to the improved bonding between cement paste and rubber aggregates as a result of surface treatment. This microstructural improvement also resulted in lower water permeability of concrete. However, the thermal conductivity and diffusivity increased when the surface treatment duration increases as there are less air voids in the samples. This study shows that, with appropriate pretreatment, a certain percentage of natural aggregates can be safely replaced with waste tyre rubber aggregates while maintaining sufficient quality of the resulting concrete.